A novel LC-MS/MS technique for identification and characterization of degradation products of Bilastine and Montelukast sodium and its greenness assessment using AGREE tool - Sapna M. Rathod, Nisarg C. Patel, Riyaz Dantroliya, Bhupendra G. Prajapati (Journal of Applied Pharmaceutical Science, 2025)
The degradation products (DPs) of Bilastine and Montelukast sodium have been identified and characterized utilizing a unique liquid chromatography-tandem mass spectrometry (LC–MS/MS) technique. Both medications are anti-allergic, and they were subjected to hydrolysis, oxidation, photolysis, and heat stimuli in accordance with International Council for Harmonisation guidelines. Under circumstances of oxidative, acidic, and base hydrolysis stress, the cited drugs exhibited widespread degradation. The drug products were stable under thermal and photolytic stress. Six DPs were found and resolved. The drug and its breakdown products were separated chromatographically on an Agilent Zorbax C18 (150 × 4.6 mm, 5μm) column with an eluent of 10 mM ammonium acetate (pH 4): acetonitrile (25:75, v/v). The hypothesized structure of DPs and their corresponding routes are based on precise mass and MS/MS fragmentation patterns; obtained using LC-ESI-TQ-MS/MS. The suggested degradant structures and pathways will be crucial for optimizing the production and quality control parameters of the pharmaceuticals under consideration.
Keywords: Bilastine, Montelukast sodium, characterization, stress degradation, LC–MS/MS, degradation pathway